A Study to Assess the Effectiveness of Structured Teaching Programme on Prevention and Management of Health Problems During Puerperium in Terms of Knowledge and Practice Among Postnatal Mothers in Sanjay Gandhi Memorial Hospital, Delhi - Ruchi Nayak; Sharda Rastogi; Anugrah Milton (Asian Journal of Medical Research, 2024)
Background: Aim: A study to assess the effectiveness of structured teaching programme on prevention and management of health problems during puerperium in terms of knowledge and practice among postnatal mothers in sanjay gandhi memorial hospital, Delhi. Material and Methods: The present study is based on the quantitative experimental approach to assess the effectiveness of Structured Teaching Programme on “prevention and management of health problems during puerperium” in terms of knowledge and practice among postnatal mothers in Sanjay Gandhi Memorial Hospital, Delhi. One group pre-test and post-test design (pre-experimental design) used to assess the effectiveness of Structured Teaching Programme on “prevention and management of health problems during puerperium” in terms of knowledge and practice among postnatal mothers. 60 postnatal mothers who delivered vaginally with or without episiotomy were included in this study. Results: The mean post-test knowledge score of postnatal mother on prevention and management of health problems during puerperium (20.13) is higher than the mean pre-test knowledge score (7.91). The median for the pre-test is 7 and median for the post-test is 20 which is fairly close to the mean of pre-test mean 7.91 and post-test mean 20.13 respectively, indicating a fairly normal probability curve, which means all the measures of central tendency coincide at the centre of the distribution to a greater extent. The standard deviation of post-test knowledge score (2.71) are more homogenous than the standard deviation of pre-test knowledge score (4.49). Conclusion: Structured teaching programme was found to be effective in improving the knowledge and practice on prevention and management of health problems during puerperium in postnatal mothers.